Accuracy assessment of stereo orientations using different types of control points with digital video plotter (DVP) software [electronic resource] - 380508 Wani Sofia Udin (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik) - Universiti Teknologi Malaysia, 2008